1998
DOI: 10.3310/hta2040
|View full text |Cite
|
Sign up to set email alerts
|

A cost-utility analysis of interferon beta for multiple sclerosis.

Abstract: A cost-utility analysis of interferon beta for multiple sclerosis. Health Technol Assessment 1998; 2(4). Health Technology Assessment is indexed in Index Medicus/Medline and Excerpta Medica/Embase. Copies of the Executive Summaries are available from the NCCHTA web site (see overleaf).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
57
2

Year Published

2005
2005
2015
2015

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(60 citation statements)
references
References 40 publications
1
57
2
Order By: Relevance
“…Eleven articles from peer-reviewed journals met the inclusion criteria [14][15][16][17][18][19][20][21][22][23][24]. The one commissioned academic report to NICE [25], its addendum [26], and all five submissions to NICE [27][28][29][30][31] were also identified as relevant.…”
Section: Systematic Review Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Eleven articles from peer-reviewed journals met the inclusion criteria [14][15][16][17][18][19][20][21][22][23][24]. The one commissioned academic report to NICE [25], its addendum [26], and all five submissions to NICE [27][28][29][30][31] were also identified as relevant.…”
Section: Systematic Review Resultsmentioning
confidence: 99%
“…The one commissioned academic report to NICE [25], its addendum [26], and all five submissions to NICE [27][28][29][30][31] were also identified as relevant. Three articles by Parkin et al [14], McNamee and Parkin [15], and Parkin et al [16] described the same underlying model and because the article published in 2000 [16] provided a less detailed summary, the primary reports used for data extraction were the original publication from 1998 [14] and the update incorporating new data published in 1999 [15]. Two articles by Bose et al [19,20] were found to describe the same model, and data were initially extracted from the 2001 article [19] and then checked against the 2002 article [20].…”
Section: Systematic Review Resultsmentioning
confidence: 99%
See 3 more Smart Citations